"الاتصال في الجماعات الإقليمية ودوره في تحسين الخدمة العمومية دراسة حالة بلدية جامعة من سنة 2011 إلى 2019 " - بوعروة, عبدالرحيم (جامعة الوادي university el-oued)
يعتبر نظام الجماعات الإقليمية من الدعائم الأساسية للمجتمعات الحديثة، فمعظم دول العالم تتوسع في تطبيقه، ذلك لاعتباره وسيلة لأداء وظائفها وأسلوب من أساليب التنظيم الإداري بمقتضاه يقسم إقليم الدولة إلى وحدات محلية، والجزائر من بين الدول التي تعتمد على هذا التنظيم الإداري فهي تجمع بين الأسلوب المركزي وتتخذ كمستويات اللامركزية الإقليمية كل من البلدية والولاية، ومع كثرة الوظائف والمهام الموضوعة على مسؤولية هذه الجماعات الإقليمية وأمام تعاملها مع شريحة كبيرة من المجتمع، وتزايد المطالب والخدمات العامة، ومواكبة للمتغيرات الاجتماعية والسياسية والاقتصادية والتطورات التكنولوجية، فإنها بحاجة ماسة إلى عملية الاتصال في أداء وظائفها وتسيير شؤونها انطلاقا من مهام وصلاحيات الموظفين على مستوى الإدارة، وخارجها من خلال تقديم الخدمات العامة، لأن هذا الأخير هو مفتاح نجاحها، وبلدية جامعة كغيرها من البلديات تسعى إلى تحسين عمليات الاتصال لترقية الخدمات العمومية تماشيا مع عصر التكنولوجيا ومع مجهودات الدولة في سن القوانين الخاصة بالجماعات الإقليمية. The system of regional groups is one of the basic pillars of modern societies. Most of the world countries are expanding its application so as to be a means to perform its functions and a method of administrative management under which the state is divided into local units. Algeria is among the countries that rely on this administrative organization it combine between the central style And are taken as regional levels of decentralization. Both the municipality and the state and with the many functions and tasks placed on the responsibility of these regional groups and as for its dealings with a large segment of society and increasing demands and public services and keep up Social, political, economic variables and technological developments they urgently need the communication process in the performance of their functions and conduct its affairs based on the functions and powers of staff at the level of management and its outside through the provision of public services. Because the latter is the key to its success and the municipality of Djamaa is like the other municipalities seeks to improve communication processes to upgrade public services with the age of technology and state groups in enacting laws on regional groups.
م.س..ع.19
Keywords: الاتصال، الجماعات الإقليمية، الخدمة العمومية، تكنولوجيا الاعلام والاتصال.; The communication, Public services Regional groups, Information and communication technology